Clinical Characteristics and Outcome of Patients With Hemorrhagic Transformation After Intravenous Thrombolysis in the WAKE-UP Trial - Jensen, Märit; Schlemm, Eckhard; Cheng, Bastian; Lettow, Iris; Quandt, Fanny; Boutitie, Florent; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; Galinovic, Ivana; Thijs, Vincent; et al. (Frontiers in Neurology, 2020)
Background: Hemorrhagic transformation (HT) is an important complication of intravenous thrombolysis with alteplase. HT can show a wide range from petechiae to parenchymal hematoma with mass effect with varying clinical impact. We studied clinical and imaging characteristics of patients with HT and evaluated whether different types of HT are associated with functional outcome. Methods: We performed a post-hoc analysis of WAKE-UP, a multicenter, randomized, placebo-controlled trial of MRI-guided intravenous alteplase in unknown onset stroke. HT was assessed on follow-up MRI or CT and diagnosed as hemorrhagic infarction type 1 and type 2 (HI1 and HI2, combined as HI), and parenchymal hemorrhage type 1 and type 2 (PH1 and PH2, combined as PH). Severity of stroke symptoms was assessed using the National Institutes of Health Stroke Scale (NIHSS) at baseline. Stroke lesion volume was measured on baseline diffusion weighted imaging (DWI). Primary endpoint was a favorable outcome defined as a modified Rankin Score 0-1 at 90 days. Results: Of 483 patients included in the analysis, 95 (19.7%) showed HI and 21 (4.4%) had PH. Multiple logistic regression analysis identified treatment with alteplase (OR, 2.08 [95% CI, 1.28-3.40]), baseline NIHSS score (OR, 1.11 [95% CI, 1.05-1.17]), DWI lesion volume (OR, 1.03 [95% CI, 1.01-1.05]), baseline glucose levels (OR, 1.01 [95% CI, 1.00-1.01]) and atrial fibrillation (OR, 3.02 [95% CI, 1.57-5.80]) as predictors of any HT. The same parameters predicted HI. Predictors of PH were baseline NIHSS score (OR, 1.11 [95% CI, 1.01-1.22]) and as a trend treatment with alteplase (OR, 2.40 [95% CI, 0.93-6.96]). PH was associated with lower odds of favorable outcome (OR 0.25, 95% [CI 0.05-0.86]), while HI was not. Conclusion: Our results indicate that HI is associated with stroke severity, cardiovascular risk factors and thrombolysis. PH is a rare complication, more frequent in severe stroke and with thrombolysis. In contrast to HI, PH is associated with worse functional outcome. The impact of HT after MRI-guided intravenous alteplase for unknown onset stroke on clinical outcome is similar as in the trials of stroke thrombolysis within a known early time-window.